Strategi Guru Pendidikan Agama Islam dalam Penguatan Nilai Akhlak untuk Mencegah Bullying Peserta Didik: Studi Kasus di SMPN 27 Medan - Muhammad Rahmadani; Hendra Kurniawan (Islamic Education, 2025)
This study aims to examine the strategies of Islamic Religious Education (IRE) teachers in fostering anti-bullying attitudes among students at SMPN 27 Medan within the framework of character education and the implementation of the Merdeka Curriculum. This qualitative research employed a case study design, with research informants consisting of Islamic Religious Education teachers, school principals, guidance and counseling teachers, and students. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using an interactive data analysis model. The findings indicate that IRE teachers apply integrative and contextual strategies, including the internalization of Islamic values through value-based learning, exemplary behavior demonstrated by teachers, empathetic teacher–student interactions, and the integration of anti-bullying values within the Pancasila Student Profile. These strategies contribute to increased student awareness, self-control, and respectful social behavior, thereby reducing bullying tendencies in the school environment. This study contributes to the development of Islamic Religious Education by reinforcing its role as a transformative and preventive approach in character education, particularly in cultivating sustainable anti-bullying attitudes aligned with contemporary curriculum policies.